Bullying. Description Of The Roles Of Victim, Bully, Peer Group, School, Family And Society - Miguel Urra Canales (Global Writing Academica Researching and Publishing, 2023)
This research defines, through an extensive literature review, the roles played by the victim, bully, peer group, school, family and society in the dynamics of bullying. Finally, we conclude that the complexity and diversity of the actors should lead us to rethink the traditional definitions of school bullying, to stake out the focus of research projects and to reconstruct prevention and action policies.